Portal hypertension. Update on pathophysiology and management - Chatila, R. (2001)
A lot has been learned about the pathophysiology of portal hypertension and its complications. This knowledge has led to vast advancements in therapy for this serious disease. I believe the future will carry more breakthroughs in therapy intercepting earlier steps in the disease process such as arresting fibrogenesis, inducing fibrinolysis or possibly targeting vascular remodeling and neovessel formation or employing hepatocytes transplantation.